Executives compensation schemes and earnings management - Syarifah Fairuz, Syed Radzuan (2011)
The purpose of this study is to investigate the association between different types of executives' compensation schemes being practised by the public listed companies in Malaysia and earnings management. Hence, I am interested in finding out whether the companies that provide short-term incentives (i.e. cash or bonus incentives) and/or long-term incentives (i.e. equity-based compensation) to their executives' directors have higher earnings management than their counterparts. Therefore, I hypothesized that there is a positive relationship between earnings management and types of compensation schemes. Firstly, I predict a higher bonus awards being granted to executives directors influence management to engage in greater earnings management. Secondly, I predict a higher equity-based compensations being granted to executives directors influence management to engage in greater earnings management. I find evidence which suggest that public listed companies who provide higher bonus incentives to their executives' directors are more likely to engage in earnings management, proxied by the level of discretionary accruals. Among the limitations of this study is that I only consider a single motivation for earnings management which is the executives' compensation contracts.